THE ROLE OF DIGITALIZATION IN THE INNOVATIVE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS - Tuychieva, Nodira (MMIT Proceedings, 2023)
This article describes the management of the processes of innovative development of higher education institutions in the conditions of the formation of an innovative economy, the role of leaders in this, approaches to the management of the higher education system in the process of globalization of higher education, and foreign experiences in this regard. The innovative competencies of the heads of higher education institutions and the main directions of their development are described. The analysis of the management of innovative, scientific-pedagogical, and scientific-research processes in higher education institutions was carried out. An attempt was made to develop some proposals and recommendations on increasing the effectiveness of the participation of leaders in the process of innovative development by monitoring conflict situations that arise in the management of innovative development processes in higher education institutions and using technologies to solve them